89 The psychiatric and cognitive profiles of children and adolescents with hypothalamic hamartomas. (4th October 2017) - Caredda, E; Wilkinson, R; Bennett, S; Cross, JH; Tisdall, M; Spoudeas, Helen; Harrison, S; Varadkar, S; Heyman, I
Abstract : Background: Hypothalamic hamartomas are rare brain malformations characterised by a syndrome of seizures, central precocious puberty, behavioural, emotional and cognitive difficulties. Behavioural and emotional symptoms often present the greatest burden of morbidity for patients and families. Due to the rarity of the disease, the heterogeneity of the presentation, and the multifactorial aetiology, prognosis is varied and management strategies are yet to be standardised. Methods: The notes of 46 paediatric cases with hypothalamic hamartomas were examined retrospectively. Demographics, behavioural and emotional symptoms, cognitive functioning, epileptic profiles, and pubertal status were recorded. ICD-10 codes for psychiatric disorder were assigned to applicable cases. Results: 61% of cases were male. The mean age at diagnosis was 4.2 years (0–14 years). 71.7% of the cases met criteria for ≥1 ICD-10 Axis 1 diagnosis (psychiatric disorder). ADHD, Generalised Anxiety Disorder and ASD were most frequent. 46% experienced characteristic rage attacks. 50% had some degree of intellectual disability, most commonly mild. 63% of cases experienced seizures. 40% had precocious puberty. Conclusion: This dataset represents one of the largest in the paediatric hypothalamic hamartoma literature. A significant proportion demonstrate psychiatric disorders and intellectual disability. Aetiology relates to a range of interacting biological and psychosocial factors. The major biological components are direct brain-behaviour effects from disrupted hypothalamic functioning and frequent seizures, alongside influence from antiepileptic medications. Psychosocial factors are those common to all chronic neurological conditions including low self-esteem, disrupted schooling and impact from family/social functioning. Currently, there are limited non-surgical evidence-based treatments for these complex cases. Defining the clinical presentation for a disease is a prerequisite to developing effective treatments. This data contributes to international efforts with this aim in mind.